KONTRIBUSI KEKUATAN GENGGAMAN DAN KELENTURAN PINGGANG TERHADAP KETEPATAN SERVICE SLICE ATLET TENIS PTL UNP - Manurizal, Lolia (Edu Research, 2016)
Based in the observation, there are some athletes doing the mistake in servicing.It can be found in doing out service, hold on the net and serve on no target. It was caused by the strength of holding and flexibility waist. The purpose of the research to find out the significance of the strength of holding and toward athletes service slice of PTL UNP. The research was the correlation. The population of the research was correlation. The population was all UNP PTL, consisted of 35 students and the sample of was 30 % by using purposive sampling. They were 20 men. Data collection used handgrips dynamometer test and Hewitt tennis achievement test and analyzed by using simple and couple product moment. The result of the research used determination coefficient. The results of the research show that 1. There was asignificance correlation between the strength of holding (X1) and service slice on target. 2. There was the significance correlation between flexibility waits (X2) and service slice on target. 3. There was the contribution between X1 and X2 toward Y itwas 32%.